An exploration of the structural, cultural and agential conditions that shape life skills teachers' responses and experiences in teaching sexuality and HIV and AIDS - Hakaala, Beatha Ndinelao (Rhodes University, Faculty of Education, Department of Education, 2015)
This paper reports findings on how Namibian secondary school Life Skills teachers are exercising their agency to teach or not to teach Sexuality and HIV and AIDS, a subject which is regarded as sensitive and has been surrounded by secrecy and has issues which are cloaked by silence and taboos. The aim of the study was to explore the structural and cultural factors that shape the responses and experiences of Life Skills teachers in teaching sexuality and HIV and AIDS. The study was conducted through observations and interviews with four full-time Life Skills teachers. Document analysis was carried out throughout the study in which lesson plans, portfolios, assessment forms, Life Skills syllabuses, schemes of works, national curriculum documents and subject policy on HIV and AIDS were analysed. The data were analysed by identifying categories, codes and themes using the analytic dualism framework, and the literature review was used to summarise the findings. The study revealed that all teachers operate in an environment that consists of the National structures such as high teacher: learner ratio in their classrooms that they have to teach Life Skills and do day to day counselling, a lack of teaching and learning support material that they should use to scaffold the learning of sexuality and HIV and AIDS, and little time allocated to Life Skills teaching. The same study also revealed that the teaching of Life Skills is hampered by the cultural structures which emerged from teachers' discourses as evidenced from the data which shows that cultural properties have powers that condition teachers in teaching sexuality and HIV and AIDS. This included learners' silence in sex-related discussion versus teachers' position; discourses on the importance of full-time Life Skills teachers in school; comfort in teaching selected topics in Life Skills; Life Skills teachers' perceptions on parents' feelings on teaching sexuality and HIV and AIDS in schools, and perceptions on the Life Skills teachers' position and teaching sexuality and sex education. While the findings revealed that teachers are conditioned by the structural and cultural conditions that acted as constraints to teaching sexuality and HIV and AIDS, the observations revealed agency on their part. The study finding depicts instances where teachers acted in agreement or in contravention of the structural and cultural pressures or conditions in their environments.
Keywords: Life skills -- Study and teaching (Secondary) -- Namibia; Sex instruction -- Study and teaching (Secondary) -- Namibia; HIV infections -- Study and teaching (Secondary) -- Namibia; AIDS (Disease) -- Study and teaching (Secondary) -- Namibia